Swot analysis of the construction of a national junior paddleboard instructor training course - Li, JiaHui (International Theory and Practice in Humanities and Social Sciences, 2025)
The purpose of this review is to analyse the current situation of junior paddleboard instructor training courses in China, and to explore their strengths, weaknesses, opportunities and challenges, in order to promote the standardised development of instructors, raise awareness of water sports safety, and encourage the consumption of fitness and sports tourism for all. This study used questionnaire data from 103 junior coaches to comprehensively assess the current situation of paddleboard coaches in China. The results of the study show that the strengths of China’s paddleboard instructor training courses lie in the abundance of university resources, frequent races and a relatively complete curriculum system; the weaknesses lie in the incomplete curriculum system, inadequate safety services, small market capacity and unclear policy on water development. Opportunities lie in national support for the development of outdoor sports, and threats are mainly the lack of training funds. The conclusion is that there is still much room for improvement in China’s paddleboard instructor training courses, and excessive competition should be avoided, focusing on experience, consumption and cultural promotion, and promoting the development of sports tourism and the industrial chain. It is recommended to enrich the course content, provide career development channels, strengthen instructor training, and establish a systematic and efficient instructor training mechanism